Book of summaries Cleveland Clinic - UTEC Summit 2024 "Accessible technologies in healthcare innovation" - Universidad de Ingeniería y Tecnología (2024)
El libro compila los resúmenes de las ponencias del Congreso Cleveland Clinic - UTEC Summit 2024 “Accessible technologies in healthcare innovation”.